Connecting Innovation and Trust through Translational Sciences – A Need for a Community Focus and Effective Education Strategies - Godoy-Vitorino, Filipa; Borrero, Michelle; Pérez-Santiago, Josué; García-García, Rubén; Gomez-Manzano, Candelaria (Puerto Rico Health Sciences Journal, 2025)
Report of a conference held in Puerto Rico, this article highlights how interdisciplinary translational science—anchored in education, public trust, and equity—can accelerate innovation in cancer therapy while empowering underserved communities through inclusive training, collaboration, and research participation.